по алгебре привести к стандартному виду


по алгебре привести к стандартному виду

Lidya777 Lidya777    1   16.02.2021 13:04    0

Ответы
Danila251008 Danila251008  18.03.2021 13:05

ответ смотри на фото...


по алгебре привести к стандартному виду
ПОКАЗАТЬ ОТВЕТЫ
alihanova1 alihanova1  18.03.2021 13:05

\frac{5}{2} x^{2} y*(\frac{3}{5}x^{2} k^3 )^2*(\frac{1}{3} yk^2)^3=

=\frac{5}{2} x^{2} y*\frac{9}{25}x^{4} k^6*\frac{1}{27} y^3k^6=

=\frac{5}{2} *\frac{9}{25}*\frac{1}{27}x^{2+4} y^{1+3} k^{6+6} =\frac{1}{30}x^{6}y^4k^{12}

ответ:     \frac{1}{30}x^{6}y^4k^{12}

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра